Doyle silicone splint insertion: endoscopy-assisted versus nasal speculum assisted - Dal,Secil Bahar (2021)
Abstract Introduction: Septoplasty and endoscopic sinus surgery are very often concurrently performed operations in otolaryngology practice. The most common complication of endoscopic sinus surgery is lateralization of the middle turbinate. In our practice intranasal stenting is done routinely with Doyle silicone splints. Objective: Retrospectively, we aimed to review the postoperative period and to document efficacy of endoscopy-assisted Doyle silicone splint application on prevention of middle turbinate lateralization. Methods: Patients who had failed medical therapy and who underwent elective primary endoscopic sinus surgery for chronic rhinosinusitis with septal deviation requiring septoplasty were included to the study. Doyle silicone splints were inserted to all patients at the end of the operation with nasal speculum or with endoscopic assistance. Groups were compared for position of the middle turbinate at the end of the postoperative first month regarding lateralization and for pain score recorded on the second postoperative day. Results: In the Doyle silicone splints applied with nasal speculum group, there were 46 patients with a total of 80 operated sides. In the endoscopy assisted group, there were 54 patients with a total of 88 operated sides. At the 1 month follow-up, the mean of middle turbinate position scores was 1.62 in the speculum-assisted group and 1.80 in the endoscopy-assisted group, the difference between two groups was found to be statistically significant. Mean of postoperative second day pain scores were worse in patients with the Doyle silicone splints applied with endoscopic assistance. This difference was found statistically significant. Conclusion: In our study, after concomitant endoscopic sinus surgery and septoplasty, less middle turbinate lateralization was observed when the Doyle silicone splints were inserted with endoscopic guidance. The surgical techniques or methods of sinus packing as well as nasal packing may have an impact on middle turbinate lateralization after concurrent septoplasty and endoscopic sinus surgery.